Human adaptive responses to climate and environmental change during the Gravettian of Lapa do Picareiro (Portugal) - Haws, Jonathan; Benedetti, Michael; Carvalho, Milena; Ellis, Grace; Pereira, Telmo; Cascalheira, João; Bicho, Nuno; Friedl, Lukas (Quaternary International, 2021)
On the Iberian Peninsula, abrupt climate shifts during the Late Pleistocene impacted human and natural systems. Our knowledge of human adaptive responses to these climatic perturbations has improved in recent years with the development of new radiocarbon techniques that have increased the temporal resolution of cultural chronologies. At the same time, new high-resolution paleoclimatic records from Greenland ice cores, deep-sea sediment cores, speleothems, and microfaunal assemblages have permitted detailed paleoenvironmental reconstructions. Combined with the archaeological record of culture change, these data sets allow for a better understanding of the nature of human socio-ecological systems during the Late Pleistocene. Here we present new data on the Gravettian occupations at Lapa do Picareiro, a cave site in Portugal with a long continuous stratigraphic sequence spanning MIS 3 and 2. The ongoing excavation of Lapa do Picareiro has revealed at least three Gravettian levels with very different patterns of raw material use and technological reduction. The Early Gravettian levels contain a quartzite flake assemblage with several refitting clusters and a small chert assemblage with nosed endscrapers and bladelet technology. The Late or Terminal Gravettian level contains carinated endscraper/core-bladelet technology, mainly quartz, with chert blade production, and a few bone tools. The faunal assemblages also have a different character. Both contain a similar range of medium and large ungulates but the earlier Gravettian has a much richer and more diverse assemblage of small animals. These combined archaeological data sets provide a new perspective on Gravettian human adaptations in response to climate shifts, especially Heinrich Event 3 and Greenland Interstadials 4 and 3. FCT: DL 57/2016/CP1361/CT0026; NSF: BCS-1420299/ BCS-1724997/ BCS-1420453/ BCS-1725015. info:eu-repo/semantics/publishedVersion